2010
DOI: 10.1590/s0102-05362010000100021
|View full text |Cite
|
Sign up to set email alerts
|

Produção de biomassa e teor do óleo essencial de cidrão em função da adubação orgânica

Abstract: Objetivou-se com a realização deste trabalho avaliar a influência da adubação orgânica na produção de massa e no teor do óleo essencial de Aloysia triphylla (L'Hérit) Britton. O experimento foi conduzido em casa de vegetação e foram aplicadas cinco doses de esterco bovino curtido: 0, 3, 6, 9 e 12 kg m-2, com quatro vasos por repetição, dispostos em delineamento inteiramente casualizado. Após 198 dias de cultivo, foi realizada a secagem em estufa e extração por hidrodestilação do óleo essencial a partir de folh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 1 publication
1
9
0
1
Order By: Relevance
“…Studies by Scheffer et al (1993) showed a positive response of A. millefolium to organic fertilization, confirming the results observed in the present study. Other studies, which have evaluated the increase in biomass production in medicinal and aromatic plants by the application of organic fertilizers, showed similar results (BRANT et al, 2010;CORRÊA et al, 2010;COSTA et al, 2008;ROSAL et al, 2011). Analysing the RDW, a quadratic response was seen, where the point of maximum accumulation was 35 g plant -1 at a dosage of 6 kg m -² for poultry manure and 28 g plant -1 at a dosage of 12 kg m -² for cattle manure (Figures 2 C and D).…”
Section: Resultssupporting
confidence: 64%
“…Studies by Scheffer et al (1993) showed a positive response of A. millefolium to organic fertilization, confirming the results observed in the present study. Other studies, which have evaluated the increase in biomass production in medicinal and aromatic plants by the application of organic fertilizers, showed similar results (BRANT et al, 2010;CORRÊA et al, 2010;COSTA et al, 2008;ROSAL et al, 2011). Analysing the RDW, a quadratic response was seen, where the point of maximum accumulation was 35 g plant -1 at a dosage of 6 kg m -² for poultry manure and 28 g plant -1 at a dosage of 12 kg m -² for cattle manure (Figures 2 C and D).…”
Section: Resultssupporting
confidence: 64%
“…The leaves of the plant emit a pleasant lemon-scent when crushed, and are used to add a lemon flavour to fish and poultry dishes, salads, jams, puddings and non-alcoholic beverages (Cunha et al, 2007(Cunha et al, , 2012. Its aromatic properties are also used in perfumes and potpourris to scent homes (Brant et al, 2010). In folk medicine, lemon verbena has been used as an antispasmodic, carminative, diuretic, digestive, and sedative agent (Pereira and Meireles, 2007;Cunha et al, 2012;Di Leo Lira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Porém, em uma segunda coleta de material, ocorreu pequena redução. Brant et al (2010) verificaram menores teores de óleo essencial em cidrão [Aloysia triphylla (L´ Hérit)] com a utilização de esterco bovino como tratamento. No entanto, nesse estudo, ressalta-se a participação desse esterco no aumento da produção da priprioca.…”
Section: Resultsunclassified